Once upon a Tim - Gibbs, Stuart, 1969- (Simon & Schuster Books for Young Readers, 2022)
With no knightly experience but plenty of pluck and an impressive vocabulary, a twelve-year-old peasant, hoping to improve his station in life, volunteers to help a cowardly prince and his not very powerful wizard rescue a princess from an evil, foul-smelling monster.